2009
DOI: 10.3382/ps.2009-00004
|View full text |Cite
|
Sign up to set email alerts
|

Genistein supplementation to the quail: Effects on egg production and egg yolk genistein, daidzein, and lipid peroxidation levels

Abstract: Genistein, a soy phytoestrogen, is a powerful antioxidant. In the present study, we investigated the effects of dietary genistein supplementation on Japanese quail (Coturnix coturnix japonica) laying performance and egg yolk contents of malondialdehyde (MDA), vitamin A, and vitamin E. Malondialdehyde is an indicator of lipid peroxidation, whereas vitamins A and E have antioxidant properties. Birds (n=150; 5 wk old) were randomly assigned to 1 of 3 groups consisting of 50 birds (5 replicates of 10) and were fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 44 publications
(64 reference statements)
0
19
3
Order By: Relevance
“…One of the principal findings in the present study was that dietary flaxseed and/or fenugreek seed supplementation significantly improved eggshell weight and eggshell thickness at the end of the egg‐laying cycle. Similarly, dietary phytoestrogens improved eggshell quality traits in Hyline brown laying hens (Gu et al, ; Ni et al, ) and quails (Akdemir & Sahin, ; Sahin et al, ) during the late laying period. The improvements in eggshell quality characteristics in the present study were probably related to increases in serum calcium concentration associated with phytoestrogens (Gu et al, ; Sahin et al, ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…One of the principal findings in the present study was that dietary flaxseed and/or fenugreek seed supplementation significantly improved eggshell weight and eggshell thickness at the end of the egg‐laying cycle. Similarly, dietary phytoestrogens improved eggshell quality traits in Hyline brown laying hens (Gu et al, ; Ni et al, ) and quails (Akdemir & Sahin, ; Sahin et al, ) during the late laying period. The improvements in eggshell quality characteristics in the present study were probably related to increases in serum calcium concentration associated with phytoestrogens (Gu et al, ; Sahin et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…These results are in agreement with Omri et al () who observed that inclusion of 0.05% fenugreek seeds increased egg weight. Several investigations illustrated that dietary phytoestrogens improved egg weight and egg quality characteristics in chickens (Saitoh, Sato, Harada, & Takita, ), ducks (Zhao et al, ) and Japanese quails (Akdemir & Sahin, ). As shown in Table , yolk colour score was significantly elevated by the dietary supplementation of flaxseeds and/or fenugreek seeds.…”
Section: Discussionmentioning
confidence: 99%
“…There was a positive effect on laying intensity in the experimental group fed 3000 mg AI per kg feed in comparison with the other experimental groups (1000 and 2000 mg AI) and the control group. Akdemir and Sahin (2009) reported that the use of 800 mg genistein per 1 kg feed increased the egg production of the quails and improved egg weight.…”
Section: Discussionmentioning
confidence: 99%
“…There is a limited number of studies concerning the effect of E 2 on Japanese quail egg production. A few studies were conducted to measure the effect of E 2 benzoate injection on egg-laying performance, whereas the majority of the studies mainly focused on the effect of phytoestrogen (daidzein and genistein)-containing diet on the egg-laying performance of the Japanese quail (Akdemir and Sahin, 2009), female chicken (Liu and Zhang, 2008) and female ducks (Zhao et al, 2005;Ni et al, 2007). In Japanese quail, the effect of external administration of E 2 on performance requires more study.…”
Section: Introductionmentioning
confidence: 99%